Hallmarks of Severe COVID-19 Pathogenesis: A Pas de Deux Between Viral and Host Factors - Rovito, Roberta; Augello, Matteo; Ben-Haim, Assaf; Bono, Valeria; d’Arminio Monforte, Antonella; Marchetti, Giulia (Frontiers in Immunology, 2022)
Two years into Coronavirus Disease 2019 (COVID-19) pandemic, a comprehensive characterization of the pathogenesis of severe and critical forms of COVID-19 is still missing. While a deep dysregulation of both the magnitude and functionality of innate and adaptive immune responses have been described in severe COVID-19, the mechanisms underlying such dysregulations are still a matter of scientific debate, in turn hampering the identification of new therapies and of subgroups of patients that would most benefit from individual clinical interventions. Here we review the current understanding of viral and host factors that contribute to immune dysregulation associated with COVID-19 severity in the attempt to unfold and broaden the comprehension of COVID-19 pathogenesis and to define correlates of protection to further inform strategies of targeted therapeutic interventions.